Imaging the lifecycle of Microsporidia sp. MB in Anopheles coluzzii from western Burkina Faso reveals octosporogony - Ewan R. S. Parry; Roland Pevsner; Beth C. Poulton; Deepak-Kumar Purusothaman; Abdelhakeem I. Adam; Sare Issiaka; Thomas H. Ant; Stephanie M. Rainey; Etienne Bilgo; Abdoulaye Diabaté; Steven P. Sinkins (mSphere)
ABSTRACT A newly discovered microsporidian, Microsporidia sp. MB (MB), was recently found to block Plasmodium falciparum transmission in Anopheles arabiensis mosquitoes from Kenya. Here, we describe the lifecycle of the first laboratory colony of Anopheles coluzzii with MB, originating from western Burkina Faso. The lifecycle of MB was explored using fluorescent in situ hybridization and confocal microscopy, facilitated by the development of optimized protocols to produce histological sections of whole adult, larval, and embryo tissues. As in An. arabiensis, transmission appears to be predominantly vertical, with MB highly localized to the ovaries across multiple lifecycle stages. MB was sparsely distributed within the majority of developing oocytes in the gravid female. After oviposition, in the majority of embryos, MB relocated to the developing gonad at the onset of tissue differentiation, suggesting a highly specialized adaptation to host tissues. Sporogony was identified for the first time in a proportion of developing oocytes and in embryos post-oviposition. Microsporidian spore characteristics were subsequently confirmed with electron microscopy. Identification of MB sporogony in eggs suggests there are alternative horizontal routes of transmission which could play an important role in developing MB as a malaria control strategy.IMPORTANCEMalaria in West Africa, caused by Plasmodium falciparum infection and spread by anopheline mosquitoes, is responsible for hundreds of thousands of deaths annually and resulted in over 120 million cases in 2022 . The transmission-blocking effect of Microsporidia sp. MB (MB) suggests its potential as an agent for combating the spread of malaria. Understanding the routes of transmission and their effect on MB in mosquito populations is crucial for its development as a control tool. The identification of MB spores reveals the potential for another avenue of transmission beyond the vertical transmission from female to offspring. Spores could also have the potential for alternative MB dissemination methods, alongside or instead of adult mosquito releases.